2011
DOI: 10.5897/ajbm11.510
|View full text |Cite
|
Sign up to set email alerts
|

Robust models for the utilization of public bus transport services in Malaysia

Abstract: Unless public transportation is efficient, affordable, clean, comfortable and convenient, people would otherwise resort to drive to their destinations. The increased in the number of private vehicles on the road in Malaysia testifies to the preference of driving to work or places of leisure for many reasons. It could also quite easily point to the ailing public transport industry save for a few developed countries that are endowed with an enviable public transport system. The overall improvement of public tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…The complete degradation of hemicellulose occurs below 350 8C, of cellulose occurs between 250 and 500 8C, and that of lignin occurs slowly over the entire temperature range, even at temperatures above 500 8C. [22,23] The research of Yang et al [8] showed an endothermic behaviour at temperatures below 400 8C for cellulose degradation (related to volatilization of the material and having a large peak around 355 8C) and an exothermic performance at temperatures above 700 8C (probably related to the cracking of functional groups present in the cellulose residues). Differently, hemicellulose and lignin presented exothermic profiles in the range of 200 to 450 8C (attributable to coal forming reactions) with peaks at 275 and 365 8C respectively.…”
Section: Sugarcane Bagasse Characterizationmentioning
confidence: 99%
“…The complete degradation of hemicellulose occurs below 350 8C, of cellulose occurs between 250 and 500 8C, and that of lignin occurs slowly over the entire temperature range, even at temperatures above 500 8C. [22,23] The research of Yang et al [8] showed an endothermic behaviour at temperatures below 400 8C for cellulose degradation (related to volatilization of the material and having a large peak around 355 8C) and an exothermic performance at temperatures above 700 8C (probably related to the cracking of functional groups present in the cellulose residues). Differently, hemicellulose and lignin presented exothermic profiles in the range of 200 to 450 8C (attributable to coal forming reactions) with peaks at 275 and 365 8C respectively.…”
Section: Sugarcane Bagasse Characterizationmentioning
confidence: 99%
“…In some big cities, public transportation such as city bus in urban areas is an optional model to deal with a variety of traffic problems including reducing the traffic jam, increasing distance reaching, and increasing mobility level (Ismail et al, 2012;Jayaraman et al, 2011;Ponnaluri, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In some parts of the world, public transportation, such as buses in urban areas, is an optional mode to overcome many traffic issues including to reduce congestion, to increase the coverage of distances and to improve the mobility levels (Abdullah, 2006;Ismail, Hafezi, Nor, & Ambak, 2012;Jayaraman, Choong, Suan, & Lin, 2011;Ponnaluri, 2011;Suwardo, Napiah, & Kamaruddin, 2009;Yaakub & Napiah, 2011a, 2011b. However, for some rural populations who are captive to buses, these are the only access modes to destinations near and far.…”
Section: Introductionmentioning
confidence: 99%